Tackling bacterial wilt in potatoes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Researchers at the Burundi Institute of Agricultural Sciences (ISABU) have devised a simple in vitro laboratory to beat the problem of bacterial wilt in potato seed production. Problems with bacterial wilt in seed stock had severely limited potato...